2009
DOI: 10.1111/j.1365-2362.2009.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Glanzmann’s thrombasthenia associated with Hairy cell leukaemia

Abstract: In the present report, a patient with Hairy cell leukaemia (HcL) who presented with bleeding diathesis was diagnosed to have acquired Glanzmann's thrombasthenia (GT). To our knowledge, this is the first report of acquired GT associated with HcL. In brief, HcL is a lymphoproliferative disorder involving the bone marrow and spleen [1] and GT is a defect caused by abnormality in GPIIb ⁄ IIIa receptor [2]. Acquired GT is an uncommon event in association with chronic limphoproliferative disorders. This may be cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An extensive review of the literature revealed that very few cases of acquired GT have been reported in association with neoplasms of lymphoid origin such as multiple myeloma, non-Hodgkin's lymphoma, and Hodgkin's disease [13]. Kannan et al found a case of hairy cell leukemia associated with acquired GT [14]. Although bleeding diathesis attributed to defective platelet function is not uncommon in CML, typical GT (e.g., a defect in platelet aggregation) has not been reported earlier in adult CML.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of the literature revealed that very few cases of acquired GT have been reported in association with neoplasms of lymphoid origin such as multiple myeloma, non-Hodgkin's lymphoma, and Hodgkin's disease [13]. Kannan et al found a case of hairy cell leukemia associated with acquired GT [14]. Although bleeding diathesis attributed to defective platelet function is not uncommon in CML, typical GT (e.g., a defect in platelet aggregation) has not been reported earlier in adult CML.…”
Section: Discussionmentioning
confidence: 99%
“…Porcelijn [3] 67, F ITP post-splenectomy (+)IgG1, Ib/IX Normal Porcelijn [3] 51, F ITP post-splenectomy (+)IgG1 Normal Kannan [43] 51, M Hairy cell leukemia Not directly detected Decreased by FCM, normal by WB Solh [16] 52, F Hypothyroidism (+), Ib/IX, IaIIa Decreased by some antibodies Raman [44] 44, M HL (+) n.d. Blickstein [45] 75, F SLE, antiphospholipid antibody syndrome, ITP postsplenectomy Not directly detected n.d.…”
mentioning
confidence: 99%